Podmioty nie-ludzkie w internecie. Przypadek rybika - Małgorzata, Jankowska (Załącznik Kulturoznawczy, 2024)
The article attempts to analyse the discourses around non-human subjects along with their ethical, aesthetic and political connotations. The case of silverfish is an example of how the Internet, as a space both shaping and reflecting cultural tendencies, transformations and conflicts, reveals social modalities of perceiving animals as subjects and/or objects. It demonstrates both extensively anthropocentric models of praxis as well as anti-anthropocentric departures from them.